2016
DOI: 10.1002/2016gl068388
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Martian thermospheric density and temperature from IUVS/MAVEN data and general circulation modeling

Abstract: Newly released Imaging Ultraviolet Spectrograph/Mars Atmosphere and Volatile EvolutioN (IUVS/MAVEN) measurements of CO2 density in the Martian thermosphere have been used for comparison with the predictions of the Max Planck Institute Martian General Circulation Model (MPI‐MGCM). The simulations reproduced (within one standard deviation) the available zonal mean density and derived temperature above 130 km. The MGCM replicated the observed dominant zonal wave number 3 nonmigrating tide and demonstrated that it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 41 publications
5
42
1
Order By: Relevance
“…The different conclusions about the relative importance of m = 2 and m = 3 tides in Lo et al () and Medvedev et al () from the same data set may be related to that fact that Lo et al () based their analysis on the peak altitude of the observed intensities, whereas Medvedev et al () relied on the CO 2 densities derived from the emissions. In principle, these two approaches should give the same results and the differences between Lo et al () and Medvedev et al () merit further investigation. It is worth noting that the coverage of the emission and density data sets differ because not all emission profiles can be confidently converted to density.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The different conclusions about the relative importance of m = 2 and m = 3 tides in Lo et al () and Medvedev et al () from the same data set may be related to that fact that Lo et al () based their analysis on the peak altitude of the observed intensities, whereas Medvedev et al () relied on the CO 2 densities derived from the emissions. In principle, these two approaches should give the same results and the differences between Lo et al () and Medvedev et al () merit further investigation. It is worth noting that the coverage of the emission and density data sets differ because not all emission profiles can be confidently converted to density.…”
Section: Resultsmentioning
confidence: 92%
“…In contrast with Lo et al () and England et al (), but consistent with the results reported here, they find that longitude perturbations are dominated by m = 3. No Fourier analysis is presented in the paper, and this statement is based on visual inspection of Figure 3 of Medvedev et al (). The perturbation amplitudes calculated by Medvedev et al () appear to be approximately a factor 2, significantly larger than found by Lo et al () and England et al () but consistent with the δ Sco occultation results.…”
Section: Resultsmentioning
confidence: 99%
“…Many modeling studies have simulated DE1 and DE2 tides and revealed their importance in controlling the longitudinal structures in the thermosphere [e.g., Bougher et al, ; Angelats i Coll et al, ; Wilson, ; Forbes and Miyahara , ; Moudden and Forbes , , ; Medvedev et al , ]. Some of these studies have found that the density amplitudes caused by these tides are ~20% at Ls = 30 – 90° in the tropics [ Bougher et al, ; Angelats i Coll et al, ; Forbes and Miyahara , ].…”
Section: Longitudinal Structuresmentioning
confidence: 99%
“…The largest difference is seen for DD2 with the mean O mixing ratio for CF depleted by as much as 20% above 180km relative to NCF, but cooling at such high altitudes is dominated by thermal conduction and horizontal advection, rather than CO 2 emission (e.g., Bougher et al 2009). Finally, non-migrating tides, which originate in the lower atmosphere and owe their existence to the topography of Mars (e.g., Forbes & Hagan 2000), provide a source of longitudinal variability in the Martian upper atmosphere (Lo et al 2015;Medvedev et al 2016). Such a possibility is also easily ruled out since the temperature variations produced by topography and crustal magnetization have different longitudinal patterns.…”
Section: Temperature Variabilitymentioning
confidence: 99%